The Implementation of Learning Optimization for the Stunting Program - Filipi Epraperas Surbakti; Iriani Ismail (Edumaspul: Jurnal Pendidikan, 2023)
Stunting is a failure to grow in children that occurs due to a lack of nutrition that can help children grow. In dealing with this incident, it is necessary to optimize the stunting reduction program. Stunting programs have a crucial aim in overcoming the problem of suboptimal child growth and development. To achieve maximum effectiveness, it is necessary to understand the things that can influence the implementation of the stunting program carried out by the Sampang Health Service. This research aims to analyze the optimization of stunting program implementation with a focus on cross-sector integration, including health, education, infrastructure and community empowerment. Research on optimizing the implementation of the stunting program uses a qualitative approach with a case study method. A qualitative approach was chosen because it is able to provide an in-depth understanding of the complexity of factors that influence the implementation of stunting programs. Through literature reviews, interviews, comprehensive observations, this research identifies the relationship between various factors and the long-term success of stunting programs in Sampang Regency. Cross-sector integration is considered a strategic approach to increase the efficiency and effectiveness of stunting programs. Some of the main findings include: the role of nutrition education in increasing mothers' awareness of the importance of child nutrition, the impact of adequate sanitation on reducing stunting prevalence, the collaboration needed to overcome structural barriers that cut across sectors, and community empowerment in designing and implementing stunting programs . Although coordination challenges and differences in priorities may arise, the long-term benefits of this approach have the potential to be in creating an environment that supports children's optimal growth and preventing future stunting.